1994
DOI: 10.1164/ajrccm.149.6.8004313
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal carbon dioxide removal technique improves oxygenation without causing overinflation.

Abstract: Extracorporeal CO2 removal combined with low frequency positive pressure ventilation (ECCO2R-LFPPV) improves gas exchange and decreases peak pressures, respiratory rates, and tidal volumes in animals and in humans. Recent evidence suggests that pulmonary barotrauma results from lung overinflation rather than from high pressures. This study was to test the hypothesis whether ECCO2R-LFPPV could improve gas exchange without causing lung overinflation, despite the use of higher levels of PEEP, when compared with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 30 publications
2
20
1
Order By: Relevance
“…20 Furthermore, risk of AL, as shown by the shape of the pressure-volume loop, was present in all adult patients with severe ARDS receiving conventional MV. 21 The frequency of AL in children with asthma, bronchiolitis, and pneumonia in this study, compares favorably with that in the literature. Studies in adult patients have shown that although there appears to be a trend toward increased survival after MV in acute asthma, ventilation of critically ill asthmatic patients continues to be associated with significant morbidity, including episodes of AL (20%), 22 and mortality.…”
Section: Discussionsupporting
confidence: 82%
“…20 Furthermore, risk of AL, as shown by the shape of the pressure-volume loop, was present in all adult patients with severe ARDS receiving conventional MV. 21 The frequency of AL in children with asthma, bronchiolitis, and pneumonia in this study, compares favorably with that in the literature. Studies in adult patients have shown that although there appears to be a trend toward increased survival after MV in acute asthma, ventilation of critically ill asthmatic patients continues to be associated with significant morbidity, including episodes of AL (20%), 22 and mortality.…”
Section: Discussionsupporting
confidence: 82%
“…Other centers have corroborated these results, resulting in 30% to 40% survival from ARF with improved conventional management,7 40% to 50% survival with ECLS, 8 and 50% to 60% survival with the two combined. [9][10][11] Based on our experience with neonatal and pediatric ECMO,12"3 and encouraged by the European results with ECCO2R, we initiated a clinical trial in 1988 consisting of a management protocol for severe ARF that included pressure-controlled inverse ratio ventilation, optimized systemic oxygen delivery, restoration of dry weight, prone positioning, and ECLS. After 2 years of pilot experience and protocol modification, we have followed this standardized approach since 1990.…”
Section: Discussionmentioning
confidence: 99%
“…Their plateau pressure commonly exceeded the upper inflection point (80% incidence) when a VT of 10 mL·kg -1 was used; however, this decreased dramatically (0-20% incidence) with VT of 5.5-7 mL·kg -1 . Using impedance plethysmography, BRUNET et al [23,24] also found an upper inflection point in ARDS patients, albeit at generally higher pressures than ROUPIE et al [7]. However, almost half the time this occurred at Paw <30 cmH 2 O.…”
Section: Assessment Of Overinflationmentioning
confidence: 93%